2010
DOI: 10.1002/etc.267
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and halogenated organic contaminants in river otters (Lontra canadensis) in New Jersey, USA

Abstract: Liver samples collected from New Jersey river otters (Lontra canadensis) in 2005 and 2007 were tested for Hg, organochlorine (OC) pesticides, polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and polybrominated diphenyl ethers (PBDEs). The highest mercury concentrations were found in otters living in the Pinelands region, where acidic soils and surface waters enhance Hg bioavailability. The highest individual Hg concentration was 19.8 µg/g wet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…BDE47 dominated the profile (78%) of these otters followed by BDE153 and BDE100 (Walker et al, 2012). In the north-eastern US, the hepatic ΣPBDE 7 concentrations (15 -8,480 mg kg -1 lw) of a different species of otter, river otters, were also dominated by BDE47 (62%) and did not show any age-or sexrelated differences in concentrations (Stansley et al, 2010). On Vancouver Island, Canada, fecal ΣPBDE 12 concentrations of river otters were low but significantly higher in otters from Victoria Harbour (0.04 -2.7 mg kg -1 lw) than from Esquimalt Harbour (0.01 -0.44 mg kg -1 lw) or outside of the harbours (0.01 -1.5 mg kg -1 lw) (Guertin et al, 2010).…”
Section: Terrestrial and Aquatic-based Mammalsmentioning
confidence: 97%
“…BDE47 dominated the profile (78%) of these otters followed by BDE153 and BDE100 (Walker et al, 2012). In the north-eastern US, the hepatic ΣPBDE 7 concentrations (15 -8,480 mg kg -1 lw) of a different species of otter, river otters, were also dominated by BDE47 (62%) and did not show any age-or sexrelated differences in concentrations (Stansley et al, 2010). On Vancouver Island, Canada, fecal ΣPBDE 12 concentrations of river otters were low but significantly higher in otters from Victoria Harbour (0.04 -2.7 mg kg -1 lw) than from Esquimalt Harbour (0.01 -0.44 mg kg -1 lw) or outside of the harbours (0.01 -1.5 mg kg -1 lw) (Guertin et al, 2010).…”
Section: Terrestrial and Aquatic-based Mammalsmentioning
confidence: 97%
“…Sex and age have been associated with varying Hg concentrations in otters (Mierle et al 2000), and yet the influence of these variables is not fully understood. Most studies report little difference in THg concentrations between males and females (Mierle et al 2000;Fortin et al 2001;Yates et al 2005;Strom 2008;Stansley et al 2010), but other studies report higher values in males (Kucera 1983) or females (Klenavic et al 2008). Yates et al (2005) observed higher mean THg concentrations in adult otters than in juveniles, whereas Mierle et al (2000) found that THg in fur changed with age in a nonlinear manner.…”
Section: Introductionmentioning
confidence: 99%
“…Due to biomagnification, otters may be exposed to greater concentrations of Hg than species feeding at lower trophic levels or those foraging on terrestrial prey. This, along with their wide distribution, makes otters ideal for studying Hg variation and impacts, both individually and at the landscape level (Kucera 1983;Mierle et al 2000;Fortin et al 2001;Yates et al 2005;Strom 2008;Stansley et al 2010;Spencer et al 2011). Moreover, there are studies showing adverse biochemical and organismal effects, and potentially population-level impacts on otters related to MeHg exposure (Wren 1991;Basu et al 2005;Sleeman et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Here we focused on the liver as it is a critical organ responsible for a majority of xenobiotic biotransformation activities. A study of otters ( n = 42) from New Jersey, USA found seven detectable PBDEs (PBDE-47, 199, 99, 153, 154, 155, and 28); mean hepatic Σ 7 PBDE concentrations averaged 10.6 ng/g wet weight (236 ng/g lipid) (ranged: 0.82–436 ng/g wet weight) (Stansley et al, 2010). In mink ( Neovison vison ) trapped in the Great Lakes region, PBDE-47, 100, 99, 153 and 154 (primary components of a commercial mixture DE-71) were found in livers at concentrations that averaged 323 ng/g lipid (range: 29.4 to 2890 ng/g lipid) (Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%